Behavior intention in using e-payment at Majlis Daerah Yan / Mohd Ashroof Masri and Siti Nor Hanisah Mat Zizan - Masri, Mohd Ashroof; Mat Zizan, Siti Nor Hanisah (2018)
This research is about the usage of users in using e-payment at Majlis Daerah Yan. The purpose of this research is to identify the extent of level of behavior intention in using epayment at Majlis Daerah Yan, the relationship between ease of use, transparency and trust which are the independent variables that could influence and lead to behavior intention in using e-payment at Majlis Daerah Yan which is the dependent variables. The total population of users is 21,536 and the number of sample chooses is 377 respondents. Researchers used non-convenient sampling technique to determine the number of sample size. In analyzing the findings, researchers used descriptive statistics, Pearson Correlation and Multiple Regression Analysis by using Statistical Package for Social Science (SPSS) version 20.0. The results indicate that there is positive significant relationship between ease of use, transparency and trust towards the behavior intention in using e-payment at Majlis Daerah Yan. The most influencing dimension that affect the the behavior intention in using epayment at Majlis Daerah Yan is transparency. This study recommend that the government utilizing the digital hub and online transactions especially in local government service delivery. In future, the study is more focusing on the wider scope to study the level of behavior intention in using e-payment at Majlis Daerah Yan.